2018
DOI: 10.1590/s0102-053620180320
|View full text |Cite
|
Sign up to set email alerts
|

Volume of cells on trays influences hydroponic lettuce production

Abstract: Lettuce seedlings used on hydroponic cultivation (NFT) are usually produced in trays with small volume, requiring two transplants: from tray to nursery and then to the definitive place. The aim of this study was to verify lettuce performance under NFT system, using seedlings produced in trays with several cell volumes (50, 40, 35, 31, 30, 29, 27, 20 and 10 cm³ cell-1). The tray volumes are considered treatments. The experimental design was completely randomized blocks, with four replicates. Seedlings were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
2
1
Order By: Relevance
“…The yield of the lettuce cv. Milena reached, on average, 2.75 kg m −2 , similar to that found by Lima et al (2018) (2.51 kg m −2 ).…”
Section: Nutrient Absorption Curve and Agronomic Evaluation Of Lettuc...supporting
confidence: 85%
See 2 more Smart Citations
“…The yield of the lettuce cv. Milena reached, on average, 2.75 kg m −2 , similar to that found by Lima et al (2018) (2.51 kg m −2 ).…”
Section: Nutrient Absorption Curve and Agronomic Evaluation Of Lettuc...supporting
confidence: 85%
“…Shoot dry mass (SDM) accumulation was, on average, 13.04 g plant −1 at 28 DAT, which is similar to that obtained by Lima et al (2018) of 12.42 g plant −1 .…”
Section: Nutrient Absorption Curve and Agronomic Evaluation Of Lettuc...supporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the production of shoot fresh mass obtained for cultivar Vanda (399.44 g plant -1 ), a larger value of shoot fresh mass was found by Lima et al (2018), who reported production of 439.50 g plant -1 for the same cultivar at harvest at 29 days after transplanting (DAT), presenting an increase of approximately 10% in relation to the present study at 23 DAT. This is due both to the greater number of days after transplantation and the greater volume of substrate used by Lima (2018) for the production of seedlings, where the seedlings developed in cells of 50 cm³ and obtained greater development of the root system, against the available 10 cm³ for the seedlings that were used in this study.…”
Section: Growth and Productioncontrasting
confidence: 59%
“…Kale is usually cultivated in soil; nevertheless, studies have demonstrated that hydroponics is an alternative, with the advantage of anticipating the harvest, which can occur in up to 30 days after seedling transplant (Noboa et al, 2019), whereas for the conventional system, the harvest begins two to three months after culture installation. Additionally, hydroponics is the technique of leafy vegetable cultivation that most grows in Brazil (Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%